Where is the missing piece of the work-family conflict? The work-[pet]family conflict - Junça Silva, A. (Human Resource Development International, 2024)
The importance of work-family conflict has been recognised for both personal and organisational outcomes. However, so far, the inclusion of pets under the umbrella of work-family conflict has been largely ignored. Considering the increasing relevance of pets for modern families, it is time to define a new concept that is rising: the work-pet-family conflict. This theoretical manuscript seeks to explain the rise of work-[pet]family conflict and to define it. It also highlights how work-[pet]family conflict should be studied in the future and its importance to deepen the understating of the intersection between pets and organisational practices.